If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -56 + -14n = -8(-6b + 1) Reorder the terms: -56 + -14n = -8(1 + -6b) -56 + -14n = (1 * -8 + -6b * -8) -56 + -14n = (-8 + 48b) Solving -56 + -14n = -8 + 48b Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + -14n = -8 + 56 + 48b Combine like terms: -56 + 56 = 0 0 + -14n = -8 + 56 + 48b -14n = -8 + 56 + 48b Combine like terms: -8 + 56 = 48 -14n = 48 + 48b Divide each side by '-14'. n = -3.428571429 + -3.428571429b Simplifying n = -3.428571429 + -3.428571429b
| 3y-21x=15 | | 6x^5+15x^3+6x=0 | | 11m-30=36 | | 2X+3(x-4)=4(2+3) | | 7x+20=3x+48 | | -24=18+6x | | 5(2x+3)=(4x+1)-2(3x+2) | | 1+1/16= | | 2n^2-2n-5=0 | | 6(2x-1)=14x-48 | | 4a+2=5.2 | | 7y-6=-55 | | 9x-2+2x=6 | | 3r+4.5=12 | | 7x+20=3x-48 | | -y+3=10 | | 4x-8=-6 | | 5x+11=-73-9x | | 3d+5d+2= | | 10s-4=8 | | -104=8(r-8) | | .3-1.6=.625m | | -6d-6=12 | | 2(x+3)=10(2+4x) | | 17=z/3-21 | | (x-5)(2x+3)-2x(x+1)=0 | | 3x-5=4x+5-x | | -4(3k-8)=128 | | 3-4+11=2 | | 4n+20=2n-4 | | x-(-19)=23 | | 5y-5x=10 |